Land Laws and Foreign Direct Investment in Myanmar: Why American Investors Need to Reconsider the Customary Rights of Smallholder Farmers - Alvin Hoi-Chun Hung (Journal of Law and Commerce, 2022)
This article looks into the issue of the government’s usage of land laws to release land from the smallholder farmers in Myanmar, which is considered not just a matter of striking a delicate balance between an individual’s customary rights of land tenure versus the need for more efficient land redistribution to sustain the country’s economic development, but also about how social stability of the rural villages in Myanmar are uprooted when the agricultural livelihood and homes of those smallholder farmers are taken away by the government’s new land policies, and how cultivation flexibility and labor employment of small-scale agriculture have been sacrificed for the introduction of large-scale farming. Given the ample investment opportunities available at both ends of the supply chain in Myanmar, American investors have to be aware of the need to sustain their corporate social responsibilities by avoiding unnecessary suffering being done to smallholder farmers in Myanmar when their lands have been confiscated to accommodate the spatial needs of foreign direct investment (FDI). This article provides recommendations to help American investors maintain their ethical stance and reputation when operating their cross-border businesses in Myanmar.